The Synergy Between Islamic Economic Values and Sustainable Entrepreneurship A Strategy for Women's Economic Empowerment in Surabaya (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study investigates the application of Islamic economic values in the economic empowerment of women through the lens of sustainable entrepreneurship in Surabaya City. Employing a qualitative approach with a case study design, the research explores the lived experiences of Muslim women entrepreneurs, the practice of sharia-compliant business models, and the integration of sustainability principles within a local urban context. Data were gathered through in-depth interviews, participatory observation, and document analysis involving key informants, including business practitioners, MSME facilitators, and Islamic economic scholars. The findings reveal that Islamic values—such as honesty, trustworthiness (amanah), social responsibility (zakat, infaq, shadaqah), and the prohibition of usury (riba)—serve as a robust moral foundation for building sustainable entrepreneurial practices. These values not only guide ethical decision-making but also foster inclusive economic participation and community-oriented business conduct. The integration of Islamic principles with sustainability efforts enables women entrepreneurs to enhance their economic capacity while simultaneously promoting environmental stewardship and social welfare. This study contributes to the theoretical discourse in Islamic economics, sustainable entrepreneurship, and gender empowerment by presenting a localized model of value-based economic development. It highlights the potential of faith-driven entrepreneurship as an alternative empowerment strategy that aligns moral integrity with long-term sustainability goals. Practically, the research offers insights for policymakers, local governments, and empowerment institutions in designing culturally grounded and socially responsive programs that support women’s economic advancement. In conclusion, the fusion of Islamic economic ethics with sustainable entrepreneurship provides a viable pathway for empowering women in urban contexts. It underscores the importance of integrating spiritual values into economic frameworks to achieve holistic development outcomes. Future research may expand this model across diverse socio-cultural settings to assess its scalability and long-term impact.